2015
DOI: 10.3892/or.2015.4048
|View full text |Cite
|
Sign up to set email alerts
|

High IGF2 expression is associated with poor clinical outcome in human ovarian cancer

Abstract: Ovarian cancer is one of the most common types of cancer in females and is the leading cause of death among gynaecological cancers in women worldwide. In the present study, we identified insulin-like growth factor 2 (IGF2) as a differentially expressed gene between cancerous and non-cancerous ovarian tissues. IGF2 was frequently increased in the human ovarian cancers when compared to the frequency in the non-cancerous ovarian tissues both at the mRNA (30/35) and protein level (61/72). The mean level of IGF2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…2A-c), PLAG1 was overexpressed in Oc tissues. The expression of IGF2 was abundant in Oc, as previously described (33,34). Of importance, PLAG1, as a transcriptional activator of IGF2, regulates expression of IGF2 (35).…”
Section: Plag1 and Igf2 Gene Expression Is Increased In Oc Degs Assosupporting
confidence: 63%
“…2A-c), PLAG1 was overexpressed in Oc tissues. The expression of IGF2 was abundant in Oc, as previously described (33,34). Of importance, PLAG1, as a transcriptional activator of IGF2, regulates expression of IGF2 (35).…”
Section: Plag1 and Igf2 Gene Expression Is Increased In Oc Degs Assosupporting
confidence: 63%
“…In relation to inflammatory markers, DII has been shown to be associated with CRP (9), IL-6 (11), TNF-a (11) and homocysteine (10). A possible common mechanism could be the effect of pro-inflammatory diet on insulin-like growth factor (IGF), which has been shown to be a promoter of carcinogenesis (40, 41) by exerting its well-established mitotic, antiapoptotic and proangiogenic effects (42). Experimental studies have shown that IGF-I protein, receptor and mRNA are expressed in ovarian cancer cells and tissues and that they are associated with progression of ovarian cancer (43).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that 9 of them were significantly associated with survival and could be considered as potential prognostic markers for GC. Among the 9 lncRNAs, high IGF2-AS expression has been reported to be associated with poor clinical outcomes in ovarian cancer (52), and ADAMTS9-AS2 has also been identified as a poor prognostic biomarker of colorectal cancer (53) and glioma (54) with DNA methyltransferase-1. However, the roles of remaining 7 lncRNAs (ABCA9-AS1, ADAMTS9-AS1, AL139002.1, AL391152.1, C15orf54, FRMD6-AS2 and VCAN-AS1) have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%